ANALISIS VEGETASI DAN VISUALISASI PROFIL VEGETASI HUTAN DI EKOSISTEM HUTAN TAHURA NIPA-NIPA DI KELURAHAN MANGGA DUA KOTA KENDARI - Zulkarnain Zulkarnain; La Ode Alimuddin; Abdur Razak (Universitas Haluoleo, 2015)
This study aims to determine the composition, structure and Visualization vegetation canopy profile of Tahura Nipa-nipa at Mangga Dua Village, Kendari City. Kelurahan Mangga Dua Kendari. This research was used mix method between partitioned track and line that placed purposive sampling crossing the contour line. The Data were analyzed to obtain information about, diversity, frequency, dominance, Important Value Index (IVI) and Shannon-Wiener Variety Index (H '). To visualize the vegetation profile using SExI-FS software version 2.1.0. The results show the amount of the collected inventory as much as 1046 individual for all species, which are clustered in 43 species and 27 families. Myrtaceae and Verbenaceae are families with the highest number of species. Castanopsis buruana and Baringtonia reticulata is species that dominate vegetation communities. The level of community diversity in the study area was moderate with an index value of the average community diversity (H ') of 2.83. Canopy stratification consists of 4 to 5 layers, this generally indicates the study sites compiled by vegetation canopy layer of relatively complete. Key words : Vegetation, Structure, Composition, Visualization Of Vegetation Profile